Handbook of porous carbon materials - Grace, Andrews Nirmala; Sonar, Prashant; Bhardwaj, Preetam; Chakravorty, Arghya (Materials horizons., 2023)
This handbook summarizes the current advancements and growth in sustainable carbonaceous porous materials for fabrication and revival of energy devices, fuel cells, sensors technology, solar cell technology, stealth technology in addition to biomedical applications. It also covers the potential applications of carbon materials in various fields such as chemical, engineering, biomedical and environmental sciences. It also confers the prospective utilization of 2D and 3D hierarchical porous carbon in different interdisciplinary engineering applications. The book discusses major challenges faced in the development of cost-effective future energy storage strategies and provides effective solutions for improvement in the performance of carbon-based materials. Given the content, this handbook will be useful for students, researchers and professionals working in the area of material chemistry and allied fields.